IMPLEMENTASI NILAI MODERASI BERAGAMA DALAM MEMBANGUN KARAKTER SOSIAL SISWA - Taufikurrahman; Zahranah, Syakira Aufa (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2023)
Islamic moderation is the justice universal value, equality, virtue and balance belonging to the Islamic religion has a strong historical basic in tradition and friends. In Indonesian context, social heterogeneity is needed to be explained as a state asset, not to be a cause of division. Referring to the matters attached above, this study is reviewed crucially to propose policies regarding education that emphasize moderate religious values. Indonesia's education policy is oriented towards brotherhood, preventing problems, and guaranteeing a safe life, this education not become a top priority. The author believes that the heterogeneous Indonesian society really needs the idea of ​​religious moderation education. This research adopts a qualitative research method, and expected to be carried out through descriptive and qualitative methods. Results and discussion value of religious moderation, among others. 1. Moderate. 2, Tolerance. 3, Balance. The implementation of the value of religious moderation is carried out through moral knowledge, feelings, actions. Implications of it’s : smiling at others, greeting, shaking hands with others, being polite, respecting elders, and loving younger ones. In behavior: respect for parents, friends, and society. The formation of social attitudes with community members, such as cleaning the village, mutual cooperation, and empathy for students when there is takziah. This shows that the implementation of character education creates good social character in students' behavior.